Analisis Faktor-Faktor yang Memengaruhi Pengembangan Ekowisata Di Sekitar Kawasan Hutan Lindung Gunung Nona Ambon Menggunakan Analytical Hierarchy Process (AHP) - Putri, Selda N E; Boreel, Aryanto; Sitanala, Merlin R (Jurnal Agrosilvopasture-Tech, 2024)
This study aims to identify factors that influence ecotourism development around the Mount Nona Ambon Protected Forest area. This research uses the AHP. approach, which is used to obtain data through interviews and questionnaires. AHP, weighting assessment data were obtained from purposively selected respondents (purposive sampling). Respondents involved in this study were land users (stakeholders), and this process involved five people who were related to the study. The study results obtained several vital points for two attractions, Siwang and Paragliding. In Siwang, tourism prioritizes accessibility as the main factor with a weight (35%), followed by the beauty and naturalness of the landscape (23%) and geophysical land (20%). Paralayang emphasizes landscape naturalness as the top priority with a weight (31%), followed by accessibility (26%), landscape beauty (25%), and geophysical land (17%). The consistency ratio (CR) value for all criteria and indicators at both attractions shows that the weighting results are consistent (CR < 0.1).